Development and validation of a prognostic nomogram for extrahepatic bile duct adenocarcinoma - Zhang, Shiyao; Cui, You; Zhao, Xinyu; Zhang, Qi; Li, Chunqiang; Huang, Qianpeng; Liu, Gang (Frontiers in Oncology, 2022)
Objective: To establish a prognostic nomogram for patients with extrahepatic bile duct adenocarcinoma. Methods: From the Surveillance, Epidemiology and End Results (SEER) database, we retrieved clinical data from 1485 patients diagnosed with extrahepatic bile duct adenocarcinoma (EBDA) between 2004 and 2015. These patients were randomly assigned to either the training or validation group in a ratio of 2:1. Cox proportional risk regression models were used to analyze the association of each variable with overall survival (OS). Univariate and multifactorial Cox regression analyses were performed to identify prognostic factors, prognostic nomograms were created based on the results of COX multifactorial regression analysis. Performance was assessed by calibration curves and receiver operating characteristic (ROC) curves. Internal validation was performed using the validation cohort. The Kaplan-Meier method was used to perform log-rank constructions for different risk groups. Results: The results indicated that age, race, N and M staging of tumor-lymph node metastases based on AJCC Version 6, surgery, and chemotherapy were independent prognostic factors for OS in patients with extrahepatic bile duct adenocarcinoma. The constructed nomograms showed decent classification in predicting both 3-year and 5-year survival rates.The calibration curves also show a high degree of agreement between the predicted and actual operating systems. Conclusions: The nomogram we constructed provides a relatively accurate and applicable prediction of survival outcome in extrahepatic bile duct adenocarcinoma patients, which helps to provide reference and guidance for patient treatment.